System Analysis of Employee Performance and Facility Supervision by the Terminal Inspection Service Unit at Tjilik Riwut Palangkaraya Airport - Erik Tirtajaya; Andityo Pujo Laksana (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Supervision of standard facilities at Palangkaraya Airport is the duty and responsibility of the Terminal Inpetion Service (TIS). The most important thing for the smooth operation of the Terminal Inspection Service (TIS) on the land side is the employee's performance in monitoring facilities with existing resources so that supervision of facilities on the land side can be carried out optimally. The purpose of this study is to determine the performance system of Terminal Inspection Service (TIS) employees for monitoring facilities at Tjiik Riwut Palangkaraya Airport. This research uses descriptive qualitative research method, the data that has been obtained will be analyzed qualitatively and described in a descriptive form. The data used in this research are primary data and secondary data. Primary data in this study included interviews with Terminal Inspection Service (TIS) unit personnel, while secondary data were obtained from Terminal Inspection Service (TIS) documents and literature. Based on the research results it is known that in carrying out their duties and responsibilities, the Terminal Inspection Service (TIS) unit still lacks personnel. Tasks that are still not handled optimally, namely supervision on the land side (Landside) namely, monitoring of Trolley facilities and air temperature in the terminal waiting room section, Trolleys are often scattered (out of place) and passengers often complain of overheating, due to the number of personnel who insufficient so that supervision of landside facilities cannot be maximized.